1990
DOI: 10.1530/acta.0.1220217
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parathyroid hormone fragments on the growth of murine mandibular condylar cartilage in vitro

Abstract: The present study showed that the fragment hPTH (1-34) is mitogenic in organ cultures of neonatal mandibular condylar cartilage, and even more so in late fetal condyles. Three fragments of hPTH were used to clarify which part of the molecule possesses a mitogenic effect alike that of the native hormone: hPTH (1-34), and (53-84). [3H]thymidine incorporation into trichloracetic acid insoluble material and quantitative autoradiography were employed in a serum-free medium to assess the effects of these fragments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…3), which means that the stimulation to proliferation could be maintained also by the somewhat older condyles. In our previous in vitro study, we observed that the midregion fragment enhanced maturation, hypertrophy, and mineralization of the chondrocytes (23). This earlier observation is in agreement with the results obtained in the present study, which showed that the proliferative effect of PTH (28 -48) was also accompanied by a rise in protein content.…”
Section: Discussionsupporting
confidence: 93%
“…3), which means that the stimulation to proliferation could be maintained also by the somewhat older condyles. In our previous in vitro study, we observed that the midregion fragment enhanced maturation, hypertrophy, and mineralization of the chondrocytes (23). This earlier observation is in agreement with the results obtained in the present study, which showed that the proliferative effect of PTH (28 -48) was also accompanied by a rise in protein content.…”
Section: Discussionsupporting
confidence: 93%
“…The involvement of 1-34 PTH, a calciotrophic fragment, in promoting calcified tissue growth has been recently demonstrated (Shurtz-Swirski et al, 1990). Our data provide evidence that this fragment of PTH also has an endocrine effect by stimulating HCG secretion by first trimester placental explants in vitro.…”
Section: Discussionsupporting
confidence: 64%
“…The secretion of a lower molecular weight fragment, namely 1-34 PTH, has also been described. This fragment, when compared to the whole molecule, acts as a mitogen on murine mandibular condylar cartilage in vitro, in addition to its calciotrophic effects which are also ascribed to the whole hormone (Milstone et al, 1989;Shurtz-Swirski et al, 1990). Recently specific binding sites for PTH were identified in the human placenta (Lafond et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PTH is rapidly degraded and has a biological half-life only of minutes in vivo. The presence of FCS abolished the inhibitory, effect of PTH on ALP activity, as was reported in the condylar organ system (28). Therefore, the influence of FCS on FFH activity was assayed.…”
Section: Discussionmentioning
confidence: 61%
“…Bone organ cultures have been used extensively to investigate the actions of vitamins, hormones, and growth factors individually on bone calcium turnover (8,20,21,23,25,26,28,33). However, in rive these agents never occur in isolation, and to realistically describe their role in the complex process of bone growth and remodeling, it is necessary to study the interactions of ealciotropic hormones and multiple mediators in vitro.…”
Section: Introductionmentioning
confidence: 99%